Mexican American Adolescents’ Sleep Patterns: Contextual Correlates and Implications for Health and Adjustment in Young Adulthood - Kuo, Sally I-Chun (J Youth Adolesc, 2014)
Late adolescence is a period of substantial risk for unhealthy sleep patterns. This study investigated the contextual correlates and health and adjustment implications of sleep patterns among Mexican American youth (N = 246; 51% female). We focused on Mexican American youth because they represent a large and rapidly increasing subgroup of the U.S. population that is at higher risk for health and adjustment problems; this higher risk may be explained, in part, by sleep patterns. Using data from 7 phone diary interviews conducted when youth averaged 18 years of age, we assessed average nighttime sleep duration and night-to-night variability in sleep duration. Guided by socio-ecological models, we first examined how experiences in the family context (time spent and quality of relationships with parents, parents’ familism values) and in extra-familial contexts (school, work, peers) were related to sleep duration and variability. The findings revealed that time spent in school, work, and with peers linked to less sleep. Further, conflict with mothers was related to greater sleep variability. Next, we tested the implications of sleep in late adolescence for health (perceived physical health, body mass index) and adjustment (depressive symptoms, risky behaviors) in young adulthood. These findings indicated that more sleep variability predicted relative decreases in health and increases in risky behaviors, and shorter sleep duration predicted relative decreases in poorer perceived health for males. The discussion highlights the significance of the transition to young adulthood as a target for sleep research and the importance of studying sleep within its socio-cultural context.